Advisory system for program selection in FTMSK / Nordaliela Mohd Rusli - Mohd Rusli, Nordaliela (2005)
There were cases where students changed to other program after a semester he or she registered to it. Most of the cases occur when a student could not perform well in the present program they registered to. They hardly understand the courses offered in the program and hardly cope-up with them. This is because they do not have the interest to gain knowledge about the course, the area of which is not their preferable area. Some programs acquire their students to be skillftil. Thus, this system is to implement the rule obtained from the study of students' educational background, interests and abilities in the development of Advisory System for Program Selection in FTMSK. The prototype is a rule - based system, developed to serve as a program recommender for future imdergraduate students in FTMSK. Methods used in the development of this project consist of gathering data from students of Information Technology Department program. The data obtained then, were analyzed using SPSS 12.0, a sophisticated software used by social scientists and related professionals for statistical analysis. The possibility of satisfying is high as the questions and elements used to develop the questions in the system is based on Holland's Self- Directed Search which is also applied in the career counseling approach. Furthermore, the samples or responder are the present students in FTMSK. Thus, this will enable the system to give the best recommendation to the users